Sarcoidosis in Nepal: Epidemiology, Clinical Presentation and Ethnic Differences - Pathak, Vikas; Pant, Hom Nath; Chokhani, Ramesh (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Sarcoidosis is a multi-system granulomatous disorder of unknown origin.The frequency and the clinical presentation of sarcoidosis vary among the geographical regions. This study is a retrospective analysis of the sarcoidosis patients diagnosed in Nepalese population. The aim of this study was to find the prevalence of sarcoidosis in Nepalese population which has high prevalence of tuberculosis and to understand the clinical profiles and ethnic differences. Materials & Methods: A retrospective chart analysis was done in all the patients from January first, 2005 to December 31st, 2010 who had abnormal chest radiograph and who were diagnosed with sarcoidosis. The study was done at Nepal Medical College Teaching Hospital and Everest Nursing Home. Results: A Forty two patients were diagnosed to have sarcoidosis over a five year period, of which 23/42 (55.0%) were females and 19/42 (45%) were males. The mean age was 36 years with minimum age being 18 years and maximum 72 years. As far as Ethnicity is concerned, 15/42 (36.0%)were Brahmins,08/42(19.0%) were Marwadi, and 07/42(17.0%) were Chhetri. The most common presenting symptom was cough 19/42 (45.0%).Out of the 42 patients, eight were being treated for pulmonary tuberculosis. Most common radiographic findings were bilateral hilar lymphadenopathy 15/42 (36.0%). Conclusion: Sarcoidosis is common in Nepal and should be considered in the differential diagnosis before treating the patient empirically for tuberculosis.